Systemic Functional Linguistics : Exploring Choice - Fontaine, Lise; Bartlett, Tom; O'Grady, Gerard (Cambridge : Cambridge University Press, 2013)
This stimulating volume provides fresh perspectives on choice, a key notion in systemic functional linguistics. Bringing together a global team of well-established and up-and-coming systemic functional linguists, it shows how the different senses of choice as process and as product are interdependent, and how they operate at all levels of language. Taking an interdisciplinary approach, it covers a range of linguistic viewpoints, informed by evolutionary theory, psychology, sociology and neuroscience, to produce a complex but unifying account of the issues. This book offers a critical examination of choice and is ideal for students and researchers working in all areas of functional linguistics as well as cognitive linguistics, second-language acquisition, neurolinguistics and sociolinguistics.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Functionalism (Linguistics); Systemic grammar